Pengembangan Sistem Pariwisata Belitung - tri wahyu widyaningsih; Didi Didi (Ultimatics : Jurnal Teknik Informatika, 2019)
This system was developed to increase the number of tourists in the Belitung region, especially in Tanjung Kelayang which is one of the Special Economic Zones (KEK) in Indonesia. Increasing the number of tourists can be done by providing technology-based facility services to tourists. The facility in question is a mobile-based application, making it easier for users to access applications. The system has been developed and tested using black box techniques with good results, and according to 31 questionnaire responses with good results of 88.71%. The system was developed using Agile, with UML system design, and Android Studio software.